Apoptosis, autophagy, ferroptosis, and pyroptosis in cisplatin-induced ototoxicity and protective agents - Dai, Dingyuan; Chen, Chao; Lu, Chen; Guo, Yu; Li, Qi; Sun, Chen (Frontiers in Pharmacology, 2024)
Cisplatin (CP) is widely used to treat various solid tumors. However, its toxicity to normal tissues limits its clinical application, particularly due to its ototoxic effects, which can result in hearing loss in patients undergoing chemotherapy. While significant progress has been made in preclinical studies to elucidate the cellular and molecular mechanisms underlying cisplatin-induced ototoxicity (CIO), the precise mechanisms remain unclear. Moreover, the optimal protective agent for preventing or mitigating cisplatin-induced ototoxicity has yet to be identified. This review summarizes the current understanding of the roles of apoptosis, autophagy, ferroptosis, pyroptosis, and protective agents in cisplatin-induced ototoxicity. A deeper understanding of these cell death mechanisms in the inner ear, along with the protective agents, could facilitate the translation of these agents into clinical therapeutics, help identify new therapeutic targets, and provide novel strategies for cisplatin-based cancer treatment.